1997
DOI: 10.1111/j.1469-7610.1997.tb01515.x
|View full text |Cite
|
Sign up to set email alerts
|

Mothers' Representations of Their Infants Assessed Prenatally: Stability and Association with Infants' Attachment Classifications

Abstract: The stability and predictive validity of classifications of mothers' representations of their infants as determined by the Working Model of the Child Interview (WMCI) were examined. Concordance between mothers' representations of their infants assessed prenatally and again one year later and infant Strange Situation (SS) attachment classifications at 12 months was also examined. WMCI classifications were stable over 12 months in 80% of mothers, compared to 51% expected by chance alone. Pregnancy WMCIs predicte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
198
1
4

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 238 publications
(212 citation statements)
references
References 28 publications
9
198
1
4
Order By: Relevance
“…Both are cause for concern, given that psychological distress during pregnancy has been associated with a range of deleterious outcomes [37][38][39] and prenatal psychological attachment to the fetus has important implications for subsequent maternal attachment to and interaction with the child. 40 Consistent with our other studies of fetal development, women who participate as volunteers tend to be relatively highly educated. As a result, the primary limitation of this study is that participants who are most concerned about the diagnosis may be overrepresented in this sample; thus, we may be overestimating the magnitude of maternal negativity to CPC detection.…”
Section: Discussionsupporting
confidence: 88%
“…Both are cause for concern, given that psychological distress during pregnancy has been associated with a range of deleterious outcomes [37][38][39] and prenatal psychological attachment to the fetus has important implications for subsequent maternal attachment to and interaction with the child. 40 Consistent with our other studies of fetal development, women who participate as volunteers tend to be relatively highly educated. As a result, the primary limitation of this study is that participants who are most concerned about the diagnosis may be overrepresented in this sample; thus, we may be overestimating the magnitude of maternal negativity to CPC detection.…”
Section: Discussionsupporting
confidence: 88%
“…In particular, they found that the relationship between pregnant women's internal working models and antenatal attachment to their infant was mediated by the future mother's representations of her own mother. Hence, from a clinical perspective, early attachment as well as current object relations both seem to express related, but not identical, aspects of internal working models Priel 1 The mediating role played by social support in the association between mothers' perceptions of early relationships and the newborn's APGAR scores suggests that mother-infant interactions might take place, on a somatic level, already before birth (Benoit et al, 1997;Priel & Besser, 2000a). Higher maternal distress levels may explain the relation of newborn's health status at birth is related to physiological concomitants of the mothers' affective state.…”
Section: Redefining Self and Othermentioning
confidence: 99%
“…Benoit et al 1997;Izard et al 1991). The interesting points to arise from the current study are that (i) the effect of expectations and evaluation of the infant on the mother-baby bond remained after depressed mood in pregnancy and postpartum were controlled for; (ii) that expectations were more moderately correlated with the mother-baby bond than postnatal evaluations; and (iii) that expectations of the infant as unadaptable or dull were associated with the mother-baby bond, yet expectations of the infant as fussy or unpredictable were not associated with the mother-baby bond.…”
Section: Implications For the Mother Baby Bondmentioning
confidence: 99%
“…There is some research evidence for this. For example, Benoit et al (1997) found that women's descriptions of their infants before birth were associated with infant security of attachment after birth. This finding implies that women's expectations of the infant during pregnancy can affect infant attachment security after birth.…”
Section: Introductionmentioning
confidence: 99%